Helicobacter pylori-Mediated Protection from Allergy Is Associated with IL-10-Secreting Peripheral Blood Regulatory T Cells - Hussain, Khiyam; Letley, Darren P.; Greenaway, A. Borgel; Kenefeck, Rupert; Winter, Jody A.; Tomlinson, William; Rhead, Joanne; Staples, Emily; Kaneko, Kazuyo; Atherton, John C.; Robinson, Karen (Frontiers in Immunology, 2016)
Helicobacter pylori infections are usually established in early childhood and continuously stimulate immunity, including T-helper 1 (Th1), Th17 and regulatory T-cell (Treg) responses, throughout life. Although known to be the major cause of peptic ulcer disease and gastric cancer, disease occurs in a minority of those who are infected. Recently there has been much interest in beneficial effects arising from infection with this pathogen. Published data robustly show that the infection is protective against asthma in mouse models. Epidemiological studies show that H. pylori is inversely associated with human allergy and asthma, but there is a paucity of mechanistic data to explain this. Since Th1 and Treg responses are reported to protect against allergic responses, we investigated if there were links between the human systemic Th1 and Treg response to H. pylori and allergen-specific IgE levels. The human cytokine and T-cell responses were examined using peripheral blood mononuclear cells (PBMCs) from 49 infected and 58 uninfected adult patients. Concentrations of total and allergen-specific plasma IgE were determined by ELISA and ImmunoCAP assays. These responses were analysed according to major virulence factor genotypes of the patients’ colonizing H. pylori strains. An in vitro assay was employed, using PBMCs from infected and uninfected donors, to determine the role of Treg cytokines in the suppression of IgE. Significantly higher frequencies of IL-10-secreting CD4+CD25hi Tregs, but not H. pylori-specific Th1 cells, were present in the peripheral blood of infected patients. Total and allergen-specific IgE concentrations were lower when there was a strong Treg response, and blocking IL-10 in vitro dramatically restored IgE responses. IgE concentrations were also significantly lower when patients were infected with CagA+ strains or those expressing the more active i1 form of VacA. The systemic IL-10+ Treg response is therefore likely to play a role in H. pylori-mediated protection against allergy in humans.